2021
DOI: 10.3389/fcell.2021.695545
|View full text |Cite
|
Sign up to set email alerts
|

TCF3 Regulates the Proliferation and Apoptosis of Human Spermatogonial Stem Cells by Targeting PODXL

Abstract: Spermatogonial stem cells (SSCs) are the initial cells for the spermatogenesis. Although much progress has been made on uncovering a number of modulators for the SSC fate decisions in rodents, the genes mediating human SSCs remain largely unclear. Here we report, for the first time, that TCF3, a member of the basic helix-loop-helix family of transcriptional modulator proteins, can stimulate proliferation and suppress the apoptosis of human SSCs through targeting podocalyxin-like protein (PODXL). TCF3 was expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…To establish the human SSC line, the human SV40 large T antigen was overexpressed in human primary GPR125-positive undifferentiated spermatogonia [ 41 ]. Immortalized human SSCs retained many primary cell properties and were positive for several SSC markers, such as PLZF, GFRA1, UCHL1, and THY1 [ 34 ]. Cultures of the human SSC line were done in DMEM/F12 (Gibco, Grand Island, NY) with 10% FBS (Gibco) and 100 unit/mL streptomycin/penicillin (Invitrogen, CA, USA) at 34℃ in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the human SSC line, the human SV40 large T antigen was overexpressed in human primary GPR125-positive undifferentiated spermatogonia [ 41 ]. Immortalized human SSCs retained many primary cell properties and were positive for several SSC markers, such as PLZF, GFRA1, UCHL1, and THY1 [ 34 ]. Cultures of the human SSC line were done in DMEM/F12 (Gibco, Grand Island, NY) with 10% FBS (Gibco) and 100 unit/mL streptomycin/penicillin (Invitrogen, CA, USA) at 34℃ in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-1908-3p promotes human SSC proliferation by targeting and degrading KLF2 mRNA [ 33 ], while CARF influences the self-renewal and proliferation of both human and mouse SSCs via the WNT signaling pathway [ 21 ]. In addition, we have previously demonstrated that the transcription factor TCF3 enhances SSC proliferation and inhibits apoptosis by promoting the transcription of genes such as PODXL [ 34 ]. However, the developmental regulatory mechanisms of human spermatogonial stem cells require additional research.…”
Section: Introductionmentioning
confidence: 99%
“…Immortalized human SSCs maintained many properties of their primary cells and expressed many markers of primary SSCs including GFRA1, RET, and promyelocytic leukemia zinc finger (PLZF). They did not express testicular endosomal cell markers such as SRY-box transcription factor 9[ 15 ]. The immortalized human SSCs were grown at 34 °C with 50 mL/L CO 2 in an incubator, and the culture medium consisted of Dulbecco’s modified Eagle’s medium (DMEM)/F12 (Gibco, Grand Island, NY, United States) supplemented with 100 mL/L fetal bovine serum (FBS; Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…According to the operating manual, the BCA Kit was utilized to detect total protein concentration. Twenty micrograms of total protein were taken from each sample for sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analysis, as previously described[ 15 ]. Detailed antibody information is listed in .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation